Analysis of the dependence between energy demand indicators in buildings based on variants for improving energy efficiency in a school building = Analiza zależności między wskaźnikami zapotrzebowania na energię w budynkach na podstawie wariantów poprawy efektywności energetycznej budynku szkoły - Skiba, Marta; Rzeszowska, Natalia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
One of the five far-reaching goals of the European Union is climate change and sustainable energy use. The first step in the implementation of this task is to reduce energy demand in buildings to a minimum by 2021, and in the case of public buildings by 2019.
Keywords: energy efficiency; public buildings; school; RES; primary energy; final energy; efektywność energetyczna; budynki użyteczności publicznej; szkoła; OZE; energia pierwotna; energia końcowa